Penilaian Ganti Kerugian dalam Pengadaan Tanah untuk Kepentingan Umum: Perspektif HAM - Agus Suntoro (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: The construction was the one of the realization of human rights, including the role of infrastructure development which was need the land. The implication was the land procurement for the public interest that have an impact on the improvement of agrarian conflicts, especially influenced by the damages assessed factors not yet viable and fair. This research was conducted to describe (1) how regulatory aspects in law number 2 of 2012 that govern the land procurement in formulating viable and fair criteria, and (2) how the assessment was conducted by the appraisal (The office of Public Assesor Agent), was given the authority to conduct an assessment of attributive replace losses seen in the perspective of human rights. This study uses qualitative methods. Primary data collection was done by interviews directed and secondary data was sourced from a variety of literature. The results of this research was the regulation of viable and equitable damages in law number 2, of 2012 was still unclear the message and in accordance with human rights norms. This was the case in the assessment aspect of damages has not been standard. This discrepancy has to do with the essence of viable and equitable reimbursement for items that have a restoration effort in school victims both material and immaterial, to rise up and to fulfill their right.Keywords: Land acquisition, infrastructure development, compensation, human rights, Indonesia.Intisari: Pembangunan merupakan perwujudan hak asasi manusia, termasuk pembangunan infrastruktur yang membutuhkan tanah. Implikasinya pengadaan tanah bagi kepentingan umum berdampak pada peningkatan konflik agraria, terutama dipengaruhi faktor ganti kerugian yang dinilai belum layak dan adil. Penelitian ini dilakukan untuk menggambarkan (1) bagaimana aspek regulasi dalam UU Nomor 2 Tahun 2012 yang mengatur pengadaan tanah bagi pembangunan untuk kepentingan umum terkait rumusan kriteria layak dan adil, dan (2) bagaimana penilaian dilakukan oleh appraisal Kantor Jasa Penilai Publik (KJPP) yang diberikan kewenangan atributif. Penelitian ini menggunakan metode kualitatif. Pengumpulan data primer dilakukan dengan wawancara terarah dan data sekunder bersumber dari berbagai literatur. Hasil penelitian ini menunjukan regulasi ganti kerugian layak dan adil dalam UU Nomor 2 Tahun 2012 belum jelas kriterianya dan sesuai dengan norma hak asasi manusia. Demikian halnya dalam aspek penilaian ganti kerugian belum ada standar dan instrumen baku. Ketidaksesuaian ini berkaitan dengan esensi layak dan adil yang memiliki unsur penggantian untuk upaya pemulihan korban terdampak baik, bersifat material dan imaterial agar mampu bangkit dan terpenuhi hak asasinya.Kata kunci: Pengadaan tanah, pembangunan infrastruktur, ganti kerugian, HAM, Indonesia.